Chemical Composition, Antioxidant and Antimicrobial Activities of Essential Oil of Warionia saharae from Oases of Morocco - Sellam, K.; Ramchoun, M.; Alem, C.; Khallouki, Farid; Moualij, B. El; Rhaffari, L. El (IntechOpen, 2012)
None